Perceived Organizational Support as a Driver of Work Engagement: Correlation Analysis in Staff Employees - Rahmawati, Sabilla; Hapsari, Maharani Tyas Budi (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Work engagement in employees can be characterized by an attitude that tends to be enthusiastic and enthusiastic in working, finishing well and cross-checking, being immersed in work, considering difficult work as a challenge that must be completed, striving for the best final results. Perceived organizational support is one of the factors that plays a role in work engagement. This research aims to examine the relationship between perceived organizational support and work engagement of company staff level employees in Solo. The novelty of this research lies in the sampling technique and research location which is different from previous researchers. The method in this research uses quantitative correlation with a sampling technique in the form of cluster random sampling, totaling 110 employees. The scale used is in the form of a Likert, namely perceived organizational support 19 items with a reliability value (α = 0.924) and work engagement 26 items with a reliability value (α = 0.881). Data analysis in this study used Pearson Product Moment with a correlation coefficient of 0.621 and sig 0.000, so the hypothesis was accepted. This means that perceived organizational support and work engagement have a positive relationship with staff level employees. The implications of this research require increasing work engagement by means of companies that need to pay attention to and develop perceived organizational support, especially for employees who have low perceived organizational support. Providing this support will create a good perception so that employee performance will be better and can achieve company goals. Work engagement pada karyawan dapat dicirikan sikap cenderung semangat dan antusias dalam bekerja, menyelesaikan dengan baik dan kroscek ulang, larut dalam pekerjaan, menganggap pekerjaan sulit sebagai tantangan yang harus diselesaikan, mengupayakan hasil akhir yang terbaik. Perceived organizational support merupakan salah satu faktor yang berperan dalam work engagement. Penelitian ini memiliki tujuan untuk meneliti hubungan perceived organizational support dengan work engagement karyawan level staff perusahaan di Solo. Kebaruan pada penelitian ini terletak pada teknik pengambilan sampel dan tempat penelitian yang berbeda dengan peneliti sebelumnya. Metode pada penelitian ini menggunakan kuantitatif korelasional dengan teknik sampling berupa cluster random sampling yang berjumlah 110 karyawan. Skala yang digunakan berbentuk Likert yaitu perceived organizational support 19 item dengan nilai reliabilitas (α = 0.924) dan work engagement 26 item dengan nilai reliabilitas (α = 0.881). Analisis data dalam penelitian ini menggunakan Pearson Product Moment dengan koefisien korelasi 0.621 dan sig 0.000 maka hipotesis diterima. Artinya perceived organizational support dan work engagement memiliki hubungan positif pada karyawan level staff. Implikasi penelitian ini perlu meningkatkan work engagement dengan cara perusahaan perlu untuk memperhatikan dan mengembangkan perceived organizational support terutama kepada karyawan yang memiliki perceived organizational yang rendah. Pemberian dukungan ini akan memunculkan persepsi yang baik sehingga kinerja karyawan akan menjadi lebih baik dan dapat mencapai tujuan perusahaan.